1992
DOI: 10.1002/jcu.1870200708
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous pleural effusions: Ultrasonic diagnosis

Abstract: Twenty patients with tuberculous pleural effusions were studied with ultrasonography. In 18 patients, ultrasonography demonstrated regular pleural thickening which was less than 1 cm except in 1 case. In 4 cases there were a few pleural nodules, whereas in 2 cases the pleural surface showed small nodularity. The latter finding may be diagnostic for a tuberculous etiology. Eighteen patients had multiple, delicate, mobile septations in the effusions, and a lattice-like appearance had formed in 6 cases. Computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…4,5 Pleural thickening and a complex septated pattern, with fibrinous strands in the pleural space producing a weblike or branching appearance, has been strongly associated with tuberculosis. [6][7][8] Chen et al 9 found a 96% specificity for tuberculous pleural effusions when differentiating between tuberculosis and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Pleural thickening and a complex septated pattern, with fibrinous strands in the pleural space producing a weblike or branching appearance, has been strongly associated with tuberculosis. [6][7][8] Chen et al 9 found a 96% specificity for tuberculous pleural effusions when differentiating between tuberculosis and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, tuberculous pleural effusions and empyema commonly had complex septated sonographic appearances. 6,[13][14][15] However, the differentiation between empyema and tuberculosis is easily made. Therefore, our objective was to focus on the lymphocyte-rich exudative pleural effusions.…”
Section: D a Bmentioning
confidence: 99%
“…The adhesive bands between the parietal peritoneum and bowel loops are often thick and rigid in peritoneal mesothelioma, unlike the fine septations seen in tuberculous peritonitis. The ascites in mesothelioma is disproportionately small in relation to the tumor dissemination and not loculated, unlike the ascites seen in tuberculous peritonitis [11].…”
Section: Discussionmentioning
confidence: 99%